Association between macular degeneration and mild to moderate chronic kidney disease: A nationwide population-based study. Issue 11 (March 2017) - Chen, Chun-Yu; Dai, Ciou-Sia; Lee, Chin-Chan; Shyu, Yu-Chiau; Huang, Ting-Shuo; Yeung, Ling; Sun, Chi-Chin; Yang, Huang-Yu; Wu, I-Wen
Abstract : Abstract: Chronic kidney disease (CKD) and macular degeneration (MD) are 2 grave diseases leading to significant disability secondary to renal failure and blindness. The 2 diseases share not only common risk factors but also similar pathogenic mechanisms to renal and retinal injuries. Previous epidemiological studies indicated association between these 2 diseases. However, this concept is challenged by recent investigations. Patients with mild to moderate CKD (n = 30, 696) between January 1, 1995 and December 31, 2005 were selected from the Taiwan National Health Insurance Database. Controls (n = 122, 784) were matched by age, gender, diabetes mellitus type 2, and hypertension status (1:4 ratios). The risk of MD was compared between the 2 groups. The mean age of patients was 54.9 ± 15.7 years. The proportion of MD was 2.7% in mild to moderate CKD patients and 1.9% in normal controls ( P < 0.001); and, 0.39% and 0.26% ( P < 0.001) in advanced MD. Mild to moderate CKD patients had higher risk for MD [adjusted odds ratio (OR), 1.301; 95% confidence interval (CI), 1.200–1.411; P < 0.001] than normal renal function subjects. The association was more pronounced for advanced MD. From all age strata (10 years increase), the presence of CKD in those patients aged less than 40 years had highest OR for all MD (OR = 2.125, 95% CI: 1.417–3.186, P < 0.001). The results were consistent in interaction terms, highlighting the importance of CKD in young age patient for risk of MD. The high risk for MD in mild to moderate CKD patients remains significant after adjustment for personal habits (alcohol drinking and smoking, model 1; OR: 1.371; 95% CI: 1.265–1.486; P < 0.001), comorbidities (dyslipidemia, cerebrovascular disease, and peripheral vascular disease, model 2; OR: 1.369; 95% CI: 1.264–1.484; P < 0.001) and all these factors (model 3; OR: 1.320, 95% CI: 1.218–1.431, P < 0.001). This association was consistent in the subanalysis, excluding those patients with diabetic retinopathy. Proper diagnosis and timely intervention should be warranted to retard visual loss of these patients.